Inclusive learning environment for pupils with special needs in general educational institution - Rozenfelde, Mārīte (Social Welfare: Interdisciplinary Approach, 2016)
The paper is focused on the analysis of the role of education’s environment in implementation of the inclusive education process for pupils with special needs: the most significant prerequisites for successful learning, development of pupils’ interaction culture and value orientation are determined; options for the presence, participation in the learning process and ensuring of achievement for all included pupils with special needs are dealt with